2019
DOI: 10.1007/s10712-019-09525-z
|View full text |Cite|
|
Sign up to set email alerts
|

Concepts and Terminology for Sea Level: Mean, Variability and Change, Both Local and Global

Abstract: Changes in sea level lead to some of the most severe impacts of anthropogenic climate change. Consequently, they are a subject of great interest in both scientific research and public policy. This paper defines concepts and terminology associated with sea level and sea-level changes in order to facilitate progress in sea-level science, in which communication is sometimes hindered by inconsistent and unclear language. We identify key terms and clarify their physical and mathematical meanings, make links between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
359
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(407 citation statements)
references
References 34 publications
1
359
0
Order By: Relevance
“…There are additionally systematic biases and hence uncertainties not accounted for in each of the observational products' formal error estimates. Using the terminology established by Gregory et al (), ocean mass changes directly observed by GRACE include both manometric changes in sea level, the change in the local mass of the ocean that incorporates the barystatic change and ocean circulation and redistribution, and the gravitational, rotational, and solid‐Earth deformation (gravitational, rotational, and deformation [GRD]) response.…”
Section: Introductionmentioning
confidence: 99%
“…There are additionally systematic biases and hence uncertainties not accounted for in each of the observational products' formal error estimates. Using the terminology established by Gregory et al (), ocean mass changes directly observed by GRACE include both manometric changes in sea level, the change in the local mass of the ocean that incorporates the barystatic change and ocean circulation and redistribution, and the gravitational, rotational, and solid‐Earth deformation (gravitational, rotational, and deformation [GRD]) response.…”
Section: Introductionmentioning
confidence: 99%
“…Regional sea-level changes (∆RSLC) result from the sum of the global and regional sea-level change components. Considering the inverse-barometer correction [53], ∆RSLC is expressed as…”
Section: Regional Sea-level Risementioning
confidence: 99%
“…where ∆Z is the sterodynamic induced sea-level change, ∆R barystatic−GRD is the barystatic-GRD-induced sea-level change (excluding GIA) (GRD: changes in Earth Gravity, Earth Rotation and viscoelastic solid-Earth Deformation) and ∆R GIA is the GIA-induced sea-level change (GIA: Glacial Isostatic Adjustment). Note that the definition of relative sea-level change (following the terminology of Gregory et al [53]) further considers local vertical ground motions, which are, however, neglected in our study. The details of the terms of Equation (1) are described in the following subsections.…”
Section: Regional Sea-level Risementioning
confidence: 99%
See 2 more Smart Citations